2013
DOI: 10.1002/stem.1389
|View full text |Cite
|
Sign up to set email alerts
|

Disease-Causing Mitochondrial Heteroplasmy Segregated Within Induced Pluripotent Stem Cell Clones Derived from a Patient with MELAS

Abstract: Mitochondrial diseases display pathological phenotypes according to the mixture of mutant versus wild-type mitochondrial DNA (mtDNA), known as heteroplasmy. We herein examined the impact of nuclear reprogramming and clonal isolation of induced pluripotent stem cells (iPSC) on mitochondrial heteroplasmy. Patient-derived dermal fibroblasts with a prototypical mitochondrial deficiency diagnosed as MELAS demonstrated mitochondrial dysfunction with reduced oxidative reserve due to heteroplasmy at position G13513A i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
103
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(109 citation statements)
references
References 37 publications
6
103
0
Order By: Relevance
“…In fact, iPSC-derived NPCs retained the entire mtDNA profile of the initial fibroblasts, including even the hypervariable D-loop region. Studies have indicated that the induction to iPSCs may be associated with heteroplasmic mtDNA alterations (Folmes et al, 2013;H€ am€ al€ ainen et al, 2013;Perales-Clemente et al, 2016;Prigione et al, 2011b). These variations appear to derive from the clonal origin of the iPSCs, because they also occur in clonally expanded fibroblasts (Kang et al, 2016;Ma et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, iPSC-derived NPCs retained the entire mtDNA profile of the initial fibroblasts, including even the hypervariable D-loop region. Studies have indicated that the induction to iPSCs may be associated with heteroplasmic mtDNA alterations (Folmes et al, 2013;H€ am€ al€ ainen et al, 2013;Perales-Clemente et al, 2016;Prigione et al, 2011b). These variations appear to derive from the clonal origin of the iPSCs, because they also occur in clonally expanded fibroblasts (Kang et al, 2016;Ma et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…OCR was measured following the sequential addition of oligomycin (0.5 g/ml), carbonyl cyanide p-trifluoromethoxyphenylhydrazone (1 M), and rotenone (0.5 M)/antimycin A (1 M). Baseline respiration rate (basal OCR Ϫ rotenone/antimycin A OCR), coupled respiration rate (basal respiration rate Ϫ oligomycin OCR), maximal respiration rate (carbonyl cyanide p-trifluoromethoxyphenylhydrazone OCR Ϫ rotenone/antimycin A OCR), and oxidative reserve (carbonyl cyanide p-trifluoromethoxyphenylhydrazone OCR Ϫ basal respiration rate) were calculated (31). Oxygen uptake in isolated mitochondria was determined using an Oroboros Oxygraph (Innsbruck, Austria) as described previously (28).…”
Section: Methodsmentioning
confidence: 99%
“…MELAS (Mitochondrial myopathy, Encephalomyopathy, Lactic Acidosis, and Stroke-like episodes) [93] was recently investigated using iPSCs. This was accomplished by several groups [93][94][95][96][97][98]. A common feature identified by these studies was that the original heteroplasmy level present in the patient fibroblasts can undergo changes before or during reprogramming.…”
Section: Ipsc Models Of Mitochondrial Neurological Diseasesmentioning
confidence: 99%